The Urgency of Strengthening Islam Moderation in the State Islamic Universities - Maimun, Maimun; Kosim, Mohammad (IAIN Ponorogo, 2022)
This study focused on how the concept of Islamic moderation was developed by PTKIN also the opportunities and challenges faced by universities. This paper aims to describe the role of state Islamic religious colleges in conceptualizing Islamic moderation and the opportunities and challenges of PTKIN in strengthening Islamic moderation in Indonesia. This research used a qualitative approach with descriptive-analytical type. Data obtained through in-depth interviews, observation, and documentation at four State Islamic Universities located in Central Java, West Nusa Tenggara, East Java, and Sulawesi. Data analysis used the Miles & Huberman analysis model, content analysis, and hermeneutic analysis. The results show that PTKIN has strengthened Islamic moderation by making it a method of thinking as well as a method of action. Conceptually, Islamic moderation is understood as values, thoughts, and actions that promote balance (in the middle) between two conflicting matters. PTKIN has enormous opportunities with human capital, institutional, political, institutional commitment, and moderate Islamic studies, as well as a very supportive environment for strengthening Islamic moderation in this country. However, the challenges also need to be addressed, both internally and externally